How do auditors perceive CEO's risk‐taking incentives?. (6th September 2013) - Fargher, Neil; Jiang, Alicia; Yu, Yangxin; Monroe, Gary
Abstract Prior literature documents that executive compensation influences managerial risk preferences through executives' portfolio sensitivities to changes in stock prices (delta) and stock‐return volatility (vega). Large deltas discourage managerial risk‐taking, while large vegas encourage risk‐taking. Theory suggests that auditors charge higher audit fees when standard audit procedures do not allow auditors to reduce audit risk including the risk arising from higher business risk. We posit and find evidence of a negative (positive) relation between CEO portfolio deltas (vegas) and audit fees. We also find a negative relation between CEO portfolio deltas and the issuance of going‐concern audit opinions (GCO).